Management of acute and chronic aortic disease during the COVID‐19 pandemic—Results from a web‐based ad hoc platform. Issue 5 (8th October 2020) - Czerny, Martin; van den Berg, Jos; Chiesa, Roberto; Jacobs, Michael; Jakob, Stephan; Jenni, Hans‐Jörg; Lorusso, Roberto; Pacini, Davide; Quintana, Eduardo; Rylski, Bartosz; Staier, Klaus; Tsilimparis, Nikolaos; et al.
Abstract: Background: To share the results of a web‐based expert panel discussion focusing on the management of acute and chronic aortic disease during the coronavirus (COVID‐19) pandemic. Methods: A web‐based expert panel discussion on April 18, 2020, where eight experts were invited to share their experience with COVID‐19 disease touching several aspects of aortic medicine. After each talk, specific questions were asked by the online audience, and results were immediately evaluated and shared with faculty and participants. Results: As of April 18, 73.3% answered that more than 200 patients have been treated at their respective settings. Sixty‐four percent were reported that their hospital was well prepared for the pandemic. In 57.7%, the percentage of infected healthcare professionals was below 5% whereas 19.2% reported the percentage to be between 10% and 20%. Sixty‐seven percent reported the application of extracorporeal membrane oxygenation in less than 2% of COVID‐19 patients whereas 11.8% reported application in 5%–10% of COVID‐19 patients. Thirty percent of participants reported the occurrence of pulmonary embolism in COVID‐19 patients. Three percent reported to have seen aortic ruptures in primarily elective patients having been postponed because of the anticipated need to provide sufficient ICU capacity because of the pandemic. Nearly 70% reported a decrease in acute aortic syndrome referrals since the start of the pandemic. Conclusion: The current COVID‐19 pandemic has—besides the stoppage of elective referrals—also led to a decrease of referrals of acute aortic syndromes in many settings. The reluctance of patients seeking medical help seems to be a major driver. The number of patients, who have been postponed due to the provisioning of ICU resources but having experienced aortic rupture in the waiting period, is still low. Further, studies are needed to learn more about the influence that the COVID‐19 pandemic has on the treatment of patients with acute and chronic aortic disease.